A uniqueness theorem for the martingale problem describing a diffusion in media with membranes - Aryasova, O.V.; Portenko, M.I. (Інститут математики НАН України, 2008)
We formulate a martingale problem that describes a diffusion process in a multidimensional Euclidean space with a membrane located on a given mooth surface and having the properties of skewing and delaying. The theorem on the existence of no more than one solution to the problem is proved.